Continuing the Journey of Education, Training and Research - Chapagain, Purushottam; Bagale, Shiba (Journal of Training and Development, 2026)
Volume 8 of the Journal of Training and Development presents six articles that explore key issues in Technical and Vocational Education and Training (TVET) in Nepal. The issue covers themes such as technology adoption in informal learning, local government financing, skills gaps in the Ayurveda sector, alignment of TVET with Sustainable Development Goals, factors influencing students’ program choices, and the integration of sustainability through greening TVET. Collectively, the studies highlight challenges in policy, funding, and skill development while suggesting strategies to enhance the effectiveness, relevance, and sustainability of TVET systems.